In Memoriam Jean Baudrillard: In Memoriam Жан Бодријар - Badarevski, Bobi; Ruskovska, Rodna (Identities: Journal for Politics, Gender and Culture, 2006)
Author(s): Bobi Badarevski | Боби Бадаревски Title (English): In Memoriam Jean Baudrillard Title (Macedonian): In Memoriam Жан Бодријар Translated by (Macedonian to English): Rodna Ruskovska | Родна Русковска Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 9-10 Page Count: 2 Citation (English): Bobi Badarevski, “In Memoriam Jean Baudrillard,” translated from the Macedonian by Rodna Ruskovska, Identities: Journal for Politics, Gender and Culture, Vol. 5, No. 2 (Summer 2006): 9-10. Citation (Macedonian): Боби Бадаревски, „In Memoriam Жан Бодријар“, Идентитети: списание за политика, род и култура, т. 5, бр. 2 (лето 2006): 9-10.